A Systematic Literature Review: The Impact of ICT on Students' Mathematical Literacy - Hermanto; Dadang Juandi; Ully Hidayati (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2022)
This research aims to describe the effect of ICT on increasing students' mathematical literacy. A systematic literature review (SLR) was used in this study because it was necessary to identify, review, evaluate, and analyze all research related to the impact of ICT on mathematical literacy skills. It is hoped that this research can provide information about the influence of ICT on mathematical literacy abilities. The Science Direct, Scopus, Eric, and Google Scholar databases were used to search for literature studies. Literature search inclusion criteria were that the research subjects were students, research results had been published in journals, and there were only a few articles from 2013 to 2022. Based on the inclusion and exclusion criteria, literature was selected and analyzed. Based on predetermined inclusion criteria, data related to keywords were obtained from 16 journal articles that were relevant and eligible for systematic review. Most research uses computers and Edmodo, and 15% each is used to improve mathematical literacy skills; this shows that ICT has a practical impact on increasing mathematical literacy.